Antimetastatic effects of thalidomide by inducing the functional maturation of peripheral natural killer cells. Issue 8 (14th July 2020) - Miyazato, Kiho; Tahara, Hideaki; Hayakawa, Yoshihiro
Abstract: Thalidomide and its analogues are known as immunomodulatory drugs (IMiDs) that possess direct antimyeloma effects, in addition to other secondary effects, including antiangiogenic, antiinflammatory, and immunomodulatory effects. Although the involvement of natural killer (NK) cells in the antitumor effects of IMiDs has been reported, it is unclear whether IMiDs inhibit cancer cell metastasis by regulating the antitumor function of NK cells. In this study, we examined the protective effects of thalidomide against cancer metastasis by focusing on its immunomodulatory effects through NK cells. Using experimental lung metastasis models, we found that pharmacological effects of thalidomide on host cells, but not its direct anticancer tumor effects, are responsible for the inhibition of lung metastases. To exert the antimetastatic effects of thalidomide, both γ‐interferon (IFN‐γ) production and direct cytotoxicity of NK cells were essential, without notable contribution from T cells. In thalidomide‐treated mice, there was a significant increase in the terminally differentiated mature CD27 lo NK cells in the peripheral tissues and NK cells in thalidomide‐treated mice showed significantly higher cytotoxicity and IFN‐γ production. The NK cell expression of T‐bet was upregulated by thalidomide treatment and the downregulation of glycogen synthase kinase‐3β expression was observed in thalidomide‐treated NK cells. Collectively, our study suggests that thalidomide induces the functional maturation of peripheral NK cells through alteration of T‐bet expression to inhibit lung metastasis of cancer cells. Abstract : In this study, we examined the antimetastatic effects of thalidomide by focusing on its immunomodulatory effects through natural killer (NK) cells. Our study suggests that thalidomide induces the functional maturation of peripheral NK cells likely through alteration of T‐bet expression, to inhibit lung metastasis of cancer cells.